The The Influence of English Listening, Reading and Speaking Skills on The Ability To Get Work For Graduates of The Business Administration Department - Erika Devie (Cita konsultindo, 2023)
This study aims to determine the English language skills of students graduating from the Department of Business Administration, Semarang State Polytechnic. This research is a quantitative approach. Respondents in this study were students who graduated from the Business Administration Department in 2022 from four study programs, namely a) Business Administration Study Program, b) Marketing Management Study Program, c) Applied Business Administration Study Program d) International Business Management Study Program consisting of a sample of 100 respondents from the entire population. The data collection techniques used were interviews and questionnaires. This study uses confirmatory factor analysis tools and maximum likehood estimation on SEM (Structural Equations Modeling) from the AMOS 24.0 (Analysis of Moment Structure) statistical package. The data collection technique uses a questionnaire with incidental sampling and snowball sampling. The results of parameter estimation in accordance with the hypothesis that Listening Skill significantly affects Get Work with a critical ratio (c.r) value of 4.007 and P-Value ***, Reading Skill has a positive effect on Get Work with a critical ratio (c.r) value of 2.194 and P-Value 0.028, Speaking Skill has a positive effect on Get Work with a critical ratio (c.r) value of 5.007 and P-Value ***. From this study it can be concluded that having good English soft skills competence as a support for success in getting a job for alumni of business administration majors, and conducting continuous self-development in accordance with technological developments.